Incident Atrial Fibrillation Hazard in Hypertensive Population. Issue 6 (June 2015) - Alves-Cabratosa, Lia; García-Gil, Maria; Comas-Cufí, Marc; Ponjoan, Anna; Martí, Ruth; Parramon, Dídac; Blanch, Jordi; Ramos, Rafel
<x xml:space="preserve">Abstract</x> Determining the risk of atrial fibrillation within the hypertensive population without ischemic vascular disease would aid in decision making on preventive approaches. Accordingly, we aimed to estimate the risk of incident atrial fibrillation in this population. We conducted an historical cohort study between July 1, 2006, and December 31, 2011, using anonymized longitudinal patient information from primary care and hospital discharge records contained in the System for the Development of Research in Primary Care database. We included 255 440 hypertensive patients, aged ≥55 years at the time of study entry. Individuals with previous atrial fibrillation, ischemic heart disease, stroke, and peripheral artery disease were excluded. To build the incident atrial fibrillation risk function, a derivation and a validation cohort were defined, representing 60% and 40% of the entire database, respectively, and a Cox proportional hazards model was fitted. Atrial fibrillation incidence was 7.24 per 1000 person-years (95% confidence interval, 7.08–7.40). The final model included age, weight, total cholesterol, heart failure, valvular heart disease, and antihypertensive treatment. Its concordance index (standard error) was 0.769 (0.004) and 0.768 (0.005) in the derivation and validation datasets, respectively. This research provides a tool, built with variables from daily clinical practice, that can be readily used in the primary care setting to predict atrial fibrillation incidence in the hypertensive population without ischemic vascular disease. The tool may help tailor individualized diagnostic and preventive care decisions.